Upaya Meningkatkan Hasil Belajar Matematika Materi Relasi Dan Fungsi Melalui Model Pembelajaran Kontekstual Pada Siswa Kelas VIII C SMP Negeri 3 Salam Semester 1 Tahun Pelajaran 2022/2023 - Uswati, Nurul (Faculty Of Education, 2022)
One of problems in learning mathematics is the weak of students in applying their knowledge to solve their daily life problems. The study of Relations and Functionsis one of theimportant learning materials that supposed to be studied in junior high levels. The application of Relations and Functionswill be a useful guide during their life. Beside that, this study is an essential knowledge that students has to know well as the basic toward the next learning materials. To solve those problems,a researchs of class action (Penelitian tindakan kelas/PTK) has been done using the contextual learning models. The purpose of this research is to improve the student’s outcomes in grade VIII C SMP Negeri 3 Salam the year of 2022/2023 using the contextual learning models. Subjects of the research are 31 students, while the source of the data was taken from the qualitative data of observing both teachers and students activities and also the quantitative data from the students test outcomes. The results are, from the first cycle research, it’s obtained that 23 students finished individuallywith 74% comprehensive classical achievement. Whereas the second cycle research shows an enhancement. The amount of students who had finished individually increase to 27 students with percentage of comprehensive classical achievement as much 87%. Due to the results, can be seen that the contextual learning models may enhance the students achievement in SMP Negeri 3 Salam grade VIII C the year of 2022/2023.